Bridging and downstaging with TACE in early and intermediate stage hepatocellular carcinoma: Predictors of receiving a liver transplant. Issue 2 (24th November 2022) - Yin, Chao; Armstrong, Samantha; Shin, Richard; Geng, Xue; Wang, Hongkun; Satoskar, Rohit S.; Fishbein, Thomas; Smith, Coleman; Banovac, Filip; Kim, Alexander Y.; He, Aiwu Ruth
Abstract: Background and Aims: In patients with surgically unresectable early and intermediate stage hepatocellular carcinoma (HCC), only liver transplant (LT) offers a cure. Locoregional therapies, such as transarterial chemoembolization (TACE), are widely used to bridge patients waiting for an LT or downstage tumors beyond Milan Criteria (MC). However, there are no formal guidelines on the number of TACE procedures patients should receive. Our study explores the extent to which repeated TACE might offer diminishing gains toward LT. Approach: We retrospectively analyzed 324 patients with BCLC stage A and B HCC who had received TACE with the intention of disease downstaging or bridging to LT. In addition to baseline demographics, we collected data on LT status, survival, and the number of TACE procedures. Overall survival (OS) rates were estimated using the Kaplan‐Meier method, and correlative studies were calculated using chi‐square or Fisher's exact test. Results: Out of 324 patients, 126 (39%) received an LT, 32 (25%) of whom had responded favorably to TACE. LT significantly improved OS: HR 0.174 (0.094‐0.322, P  < .001). However, the LT rate significantly decreased if patients received ≥3 vs < 3 TACE procedures (21.6% vs 48.6%, P  < .001). If their cancer was beyond MC after the third TACE, the LT rate was 3.7%. Conclusions: An increased number of TACE procedures may have diminishing returns in preparing patients for LT. Our study suggests that alternatives to LT, such as novel systemic therapies, should be considered for patients whose cancers are beyond MC after three TACE procedures. Abstract : The ultimate goal in treating patients with early and intermediate stage HCC is liver transplantation; surgery is the only means of a cure in HCC. Locoregional therapies such as transarterial chemoembolization (TACE) has historically played a crucial role in optimizing patients for liver transplantation. However, we call into question whether these patients still derive the greatest benefit from repeated TACE procedures, particularly in the current landscape of new and effective systemic therapy options.